2010
DOI: 10.1007/s11207-010-9660-y
|View full text |Cite
|
Sign up to set email alerts
|

Vlasov – Maxwell, Self-consistent Electromagnetic Wave Emission Simulations in the Solar Corona

Abstract: 1.5D Vlasov-Maxwell simulations are employed to model electromagnetic emission generation in a fully self-consistent plasma kinetic model for the first time in the solar physics context. The simulations mimic the plasma emission mechanism and Larmor drift instability in a plasma thread that connects the Sun to Earth with the spatial scales compressed appropriately. The effects of spatial density gradients on the generation of electromagnetic radiation are investigated. It is shown that 1.5D inhomogeneous plasm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…In Ref. [8] it was shown that when an electron beam, with the properties similar to considered here, is injected perpendicular to the background magnetic field, the beam excites electrostatic, standing waves, oscillating at local plasma frequency, in the beam injection spatial location. Here physical situation is different in that now the beam is injected along the magnetic field which is more plausible for the type III radio bursts.…”
Section: A Inhomogeneous Plasma Without An Electron Beammentioning
confidence: 81%
See 4 more Smart Citations
“…In Ref. [8] it was shown that when an electron beam, with the properties similar to considered here, is injected perpendicular to the background magnetic field, the beam excites electrostatic, standing waves, oscillating at local plasma frequency, in the beam injection spatial location. Here physical situation is different in that now the beam is injected along the magnetic field which is more plausible for the type III radio bursts.…”
Section: A Inhomogeneous Plasma Without An Electron Beammentioning
confidence: 81%
“…Thus, we conclude that the equilibrium without the electron beam is fairly stable (apart from the low level EM drift wave noise). In this section we present the results when we inject the electron beam along the background magnetic field [8], when the beam is relatively dense (n b /n e ≈ few 10 −2 ), the electron number density perturbation is dominated by a wake created by the beam. In Ref.…”
Section: A Inhomogeneous Plasma Without An Electron Beammentioning
confidence: 99%
See 3 more Smart Citations